Assessing the Authority of the General Election Supervisory Agency in Maintaining the Neutrality of the State Civil Apparatus in the 2020 Regional Elections - Muis, Andi Asfarida (Estudiante Law Journal, 2024)
The research objective to be achieved in the preparation of this study is to analyze the authority of the General Election Supervisory Agency in maintaining the neutrality of the State Civil Apparatus in the implementation of the 2020 regional head elections in Gorontalo Regency.  Jenis this research is Sociological Juridical research and the approaches used by researchers in compiling this research are, among others: The Statutory Approach (Statue Approach); cathe se approach (case approach);  and Comparative Approach.  The results of this study show that Dalam carried out the supervision stage of General Election Supervisory Agency has carried out socialization with all ASNs, the signing of Mou agreement, ents and meetings with each OPD in each Village and Environment in Gorontalo Regency. However, every implementation of the General Election Supervisory Agency regional elections still receives reports of alleged violations from members of the General Election Supervisory Agency supervisory as well as from the public that the ASN has violated related regulations on ASN Neutrality which has resulted in the smearing of democracy in terms of the neutrality of the ASN, this arises due to the presence of inhibiting factors and supporting factors that can measure how far the success of the role possessed by General Election Supervisory Agency in enforcing the perinsip Neutrality of ASN in the Regional Elections  Gorontalo Regency